Introduction of complementary food to infants within the first six months postpartum in rural Vietnam - Duong, Dat Van; Binns, Colin; Lee, Andy (Taylor and Francis Group, 2005)
Aim: To document the introduction of complementary food and factors influencing the decision to feed infants with solid food within 6 mo postpartum in rural Vietnam. Methods: A longitudinal study of 463 women who gave birth during August-October 2002 was conducted. Results: An early introduction of complementary food was found, which increased from 16.4% at week 1 to 56.5% at week 16 and nearly 100% at week 24. Home-cooked solid food was introduced by 4.8%, 40.9% and 74.3% of women at weeks 1, 16 and 24, respectively. Logistic regression analysis found that at week 24 postpartum, it was less likely for the infant to be fed with solid food if the mother was a farmer (OR 0.52, 95% CI: 0.18-0.95) and passed secondary school (OR 0.28, 95% CI: 0.10-0.54), whose husband was satisfied with the infant's sex (OR 0.30, 95% CI: 0.17-0.53), her mother-in-law preferred exclusive breastfeeding (OR 0.18, 95% CI: 0.04-0.75), or her friends practised exclusive breastfeeding (OR 0.41, 95% CI: 0.16-1.10). However, infants were likely to be fed with solid food when their parents had higher income and lived independently (OR 1.76, 95% CI: 1.01-3.06).Conclusion: Community mobilization for sharing the workload with women could help them to cope with employment and breastfeeding.